Aplicação subsidiária do processo comum nas fases postulatória e instrutória do processo de conhecimento do trabalho - Monteiro, Carlos Augusto Marcondes de Oliveira (2007)
This study had for purpose the analysis of phases of the individual process of the work front, of form o the common process. To reach this objective a boarding of the hypotheses was carried through where was to demonstrate that beyond the omission hypotheses, also it is possible to invoke the common process when constitutional. For better understanding it was discoursed on each constitutional principle, well ases of the individual process became, detaching the procedural acts, distinguishing them from facts the judges, the parts and of third. After, a study of the distribution of process e became modalities foreseen in the CLT and to the that foreseen in the CPC, finishing chapter treating to the process of the work. Still it was looked to trace an analysis of the complaint brief, in its , value of the cause and petitions), the amendment hypotheses, amends and denial of hypotheses of answers of the complained one, mainly the exception, plea and reconvention, tracing ne also demonstrated that the accomplishment of the hearing must be reviewed by the judges of s are guaranteed and finally, was about the tests in the process of the work